Analysis of The Relationship Between Oral Health Maintenance Behavior of Prisoners on DMFT and OHIS Scores - Aldilawati, Sari; Ilmianti; Hidaya, Noer (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Every human being, including prisoners, has the right to general health and dental health. Prisoners have the right to receive treatment, both spiritual and physical, namely health services. Dental and oral health status is a health problem in Indonesia that has received little attention. In West Sulawesi Province, 68.4% had dental problems, 78.3% received treatment, and 93.0% never sought treatment. Based on research results, dental and oral health care facilities in prisons are still very limited, making it difficult for prisoners to get treatment. Therefore, researchers want to know the behavior and dental health status of prisoners at the research location. Materials and Methods: This study used an analytical observational design with a cross-sectional research design. Sampling was carried out by purposive sampling, where the samples that met the inclusion criteria were 109. Results and Discussion: Oral health maintenance behavior in the sufficient category is 47 prisoners (37.06%), dental caries status in the Decay Missing Filled-Teeth (DMF-T) score category is very high, namely 41 prisoners (37.06%), oral hygiene status and Oral Hygiene Index Simplified (OHI-S) category is moderate, 79 prisoners (72.48%). The results of the correlation or relationship test using Spearman, p-value <0.001, which means that there is a relationship between oral health behavior with DMF-T and OHI-S scores. Conclusion: From the results of the study, it can be concluded that there is a relationship between oral health maintenance behavior and DMFT and OHI-S caries scores in prisoners at Class IIB Polewali Mandar Prison, West Sulawesi.